The presidency - Quiri, Patricia Ryon (New York Children's Press, 1998)
Examines various aspects of the presidency, providing some historical background and describing the election, duties, and daily activities of the president
American Corner
Includes bibliographical references (p. 44) and index
11
Keywords: Presidents -- United States -- Juvenile literature; Presidents